Use of Novel Antibiograms to Determine the Need for Earlier Susceptibility Testing and Administration for New β-Lactam/β-Lactamase Inhibitors in the United States - Kenneth P. Klinker; Levita K. Hidayat; Eric Wenzler; Joan-Miquel; Mary Motyl; C. Andrew DeRyke; Karri A. Bauer (MDPI AG, 2022)
Antimicrobial resistance is a global public health threat, and gram-negative bacteria, such as Enterobacterales and Pseudomonas aeruginosa, are particularly problematic with difficult-to-treat resistance phenotypes. To reduce morbidity and mortality, a reduction in the time to effective antimicrobial therapy (TTET) is needed, especially among critically ill patients. The antibiogram is an effective clinical tool that can provide accurate antimicrobial susceptibility information and facilitate early antimicrobial optimization, decrease TTET, and improve outcomes such as mortality, hospital length of stay, and costs. Guidance is lacking on how to validate the susceptibility to new antibacterial agents. Commonly used traditional and combination antibiograms may not adequately assist clinicians in making treatment decisions. Challenges with the current susceptibility testing of new β-lactam/β-lactamase inhibitor combinations persist, impacting the appropriate antibacterial choice and patient outcomes. Novel antibiograms such as syndromic antibiograms that incorporate resistant gram-negative phenotypes and/or minimum inhibitory concentration distributions may assist in determining the need for earlier susceptibility testing or help define an earlier optimal use of the new β-lactam/β-lactamase inhibitors. The purpose of this review is to emphasize novel antibiogram approaches that are capable of improving the time to susceptibility testing and administration for new β-lactam/β-lactamase inhibitors so that they are earlier in a patient's treatment course.